Construction and Identification of Cold Tolerance in Different Broccoli Cultivars at the Seedling Stage - Dongna Wen; Fengqing Han; Yongyu Zhao; Yuxiang Liu; Yumei Liu; Jianxin Huang; Zhansheng Li (Agronomy, 2024)
This study aimed to develop a systematic method for assessing the cold tolerance of broccoli seedlings, which is helpful to evaluating the cold tolerance of broccoli cultivars. We selected 14 classical broccoli cultivars and evaluated their cold tolerance by examining physiological indicators including the levels of cold resistance, electrical conductivity, malondialdehyde (MDA), soluble sugar, and hydrogen peroxide (H2O2). The results showed that there were significant differences in detected characteristics in all cultivars after cold stress during the seedling stage (p < 0.05). Among them, Meiqing had the strongest cold tolerance, followed by King 11, Zhongqing 15, Meiao 7172, Zhongqing 318, Zheqing 80, Zhongqing 16, Zhongqing 319, and Lvxiong 90. However, Zhongqing 11, Yanxiu, Qianghan, and Feicui 5, showed the worst cold tolerance (all died). Pearson correlation analysis indicated that there was a significantly negative correlation between the cold tolerance and the electrical conductivity during broccoli seedling stage, with a correlation coefficient of −0.586 (p < 0.05). At the same time, we found that the electrical conductivity of all broccoli cultivars showed a positive correlation with the MDA and soluble sugar levels, with the correlation coefficients 0.650 and 0.573, respectively (p < 0.05). This study not only firstly provides a fundamental method for evaluating the cold tolerance in different broccoli genotypes and the other cruciferous vegetables, but also offers a scientific evidence explaining the cold tolerance of the Meiqing, King 11, and Zhongqing 15 cultivars widely cultivated in China.